PENGARUH PRAKTEK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KEBERLANJUTAN PERUSAHAAN PT. MANADO SEJATI PERKASA - Omega Gratia Anita Karisoh Gratia Anita Karisoh; Riane Johnly Pio; Sandra Ingried Asaloei (JURNAL ADMINISTRASI BISNIS, 2017)
This study aims to determine the effect of human resourcesmanagement practices on the sustainability of the company at PT. Manado SejatiPerkasa. In this study, researchers used Armstrong’s theory to describe thepractice of human resource management and De Geus to describe the company’ssustainability. The method used in this research is quantitative descriptive methodby spreading the questionnaire 50 respondents who become the sample in thisresearch. Data collection was done with questionnaires that have been tested forvalidity and reliability. And data analysis us is descriptive and inferentialstatistic, consisting of correlation coefficient and simple regression done by usingprogram SPSS for windows version 23.0. The results show that there is asignificant influence beetwen the practice of human resource management on thesustainability of the company. From th results obtained require PT. ManadoSejati Perkasa to maximize human resource management pratices.Keyword: Practices of human resource management, corporate sustainability.